Transient flow analysis in a Roots blower: Experimental and numerical investigations. (1st December 2019) - Singh, Gursharanjit; Sun, Shuaihui; Kovacevic, Ahmed; Li, Qianhui; Bruecker, Christoph
Highlights: Roots blower flow field is highly transient and difficult to capture. Instantaneous PIV technique is a suitable method to capture its flow field. The transient flow is dependent on the flow mechanisms initiated by axial and interlobe leakages. Abstract: It is widely acknowledged that rotary positive displacement machines exhibit highly unsteady flow fields that affect their performance. The presence of the operational clearances impacts this unsteady flow field and further affects the performance. However, the exact nature of these unsteady flow mechanisms remains largely unknown that necessitates both detailed experimental investigations and computational modelling. Thus, the present study employs both optical visualization and unsteady Reynolds-Averaged Navier Stokes (URANS) computational modelling methods while focussing on investigating the transient flow field inside a Roots blower, a general type of the rotary positive displacement machine. Straight lobes in a Roots blower provide convenient optical access to experimentally analyse internal flow and compare it with the predictions obtained by standard computational models. In the first part of this paper, this study covers the low-speed experimental investigations using i) High-Speed Camera (HC), ii) the continuous High-Speed Particle Image Velocimetry (CPIV) and, iii) the instantaneous PIV (IPIV) obtained with a double pulse laser and a double shutter camera. Relative merits from these techniques are discussed with respect to the Roots blower unsteady flow mechanisms. In addition, computational analyses are performed using a combination of in-house and commercial modelling methods and the results are compared against the experiments. The results confirm the existence of highly three-dimensional and unsteady flow field where certain distinct flow mechanisms originating from the operational clearances impact the performance of the Roots blower. The study also highlights challenges of the experimental and computational methods used for evaluation of positive displacement machines that impact the accuracy of results.